Complete Healing of a Giant Wart in a Severely Immune-Compromised Patient with HIV Infection Treated with Acupuncture - T. Ursini; E. Polilli; G. Congedo; M. Tontodonati; F. Di Masi; E. Mazzotta; G. Parruti; L. Pippa (Karger Publishers, 2011)
Giant warts are infrequent dermatological viral infections caused by Papillomavirus (HPV) in immune-compromised patients. Treatment may often be difficult and unsatisfactory, either by surgery or cytotoxic agents, because of poor immune control of viral activity in such hosts. Here we report on the case of a patient with advanced and persistent immune suppression caused by HIV disease, who developed a monstrous wart covering the entirety of the radial district of his right hand. He was completely healed after a long treatment with traditional Chinese acupuncture, in spite of minimal immune recovery induced by efficacious antiretroviral therapy. To the best of our knowledge, therefore, the present report may be the first direct clinical evidence that acupuncture may be effective in the treatment of cutaneous warts also in HIV-infected patients.